Location-based services - Schiller, Jochen H.; Voisard, Agnαes (San Francisco, CA : Morgan Kaufmann Publishers, 2004)
Location-based services (LBS) are a new concept integrating a users geographic location with the general notion of services, such as dialing an emergency number from a cell phone or using a navigation system in a car. Incorporating both mobile communication and spatial data, these applications represent a novel challenge both conceptually and technically. The purpose of this book is to describe, in an accessible fashion, the various concepts underlying mobile location-based services. These range from general application-related ideas to technical aspects. Each chapter starts with a high level of abstraction and drills down to the technical details. Contributors examine each application from all necessary perspectives, namely, requirements, services, data, and scalability. An illustrative example begins early in the book and runs throughout, serving as a reference. This book defines the LBS field and identifies its capabilities, challenges, and technologies. The contributors are recognized experts from academia and industry. Coverage includes navigation systems, middleware, interoperability, standards, and mobile communications. A sample application, the "find-friend" application, is used throughout the book to integrate the concepts discussed in each chapter.
General aspects of location-based services / Sarah Spiekermann -- Case study : development of the Find friend application / Mark Strassman and Clay Collier -- Navigation systems : a spatial database perspective / Shashi Shekhar ... [et al.] -- Middleware for location-based services / Hans-Arno Jacobsen -- Database aspects of location-based services / Christian Jensen -- LBS interoperability through standards / Lance McKee -- Data collection / Joerg Roth -- Data transmission in mobile communication systems / Holger Karl.
Includes bibliographical references and index.
Keywords: Mobile computing; Electronic books